2006
DOI: 10.1111/j.1365-2109.2006.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of partially dehulled and extruded sunflower meal for post-smolt Atlantic salmon (Salmo salar L.) in sea water

Abstract: This study determined the digestibility of protein in partially dehulled sunflower meal (SFM) and then, as the main goal, the nutritive value of high‐temperature extruded (≤149°C) partially dehulled SFM (SFMEX) for post‐smolt Atlantic salmon Salmo salar in sea water. The digestibility study was conducted using the settling column approach (‘Guelph system’) for faeces collection as described by Hajen, Higgs, Beames and Dosanjh. In the nutritive value study, triplicate groups of 50 salmon (mean weight ∼116 g) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
5
18
0
1
Order By: Relevance
“…Regarding feed efficiency parameters, Sánchez Lozano et al (2007) showed an increment in FI whereas Olvera Novoa et al (2002) reported a reduction in FI as the SFM substitution increased. Gill et al (2006) reported similar results to our study with regard to PER.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Regarding feed efficiency parameters, Sánchez Lozano et al (2007) showed an increment in FI whereas Olvera Novoa et al (2002) reported a reduction in FI as the SFM substitution increased. Gill et al (2006) reported similar results to our study with regard to PER.…”
Section: Discussionsupporting
confidence: 91%
“…In body composition, only fish fed diet with11.7% SFM inclusion obtained the lowest value in CP indicating that the vegetal meal did not affect body composition, which was similar to the results of Gill et al (2006) and Sánchez Lozano et al (2007) results. However, OlveraNovoa et al (2002) obtained statistical differences not only in CP but also in CL, ash and humidity as a consequence of SFM inclusion leading to a reduction of CP and an increase in CL and ash content.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations